Ecological Problem: Content, Essence and Preconditions - Kalenda, Česlovas (Problemos, 2000)
The article contains discussion of the present-day ecological problem (crisis) as the result brought about by interaction of objective and subjective factors. Taking into consideration an objective (socionatural) point of view, the global ecological crisis is a result of the accumulated contradictions between a human (culture) and nature (biosphere), between technical and technological development and natural evolution. A subjective aspect of origin of the ecological problem (and solution thereof) is being analysed on the metaphysical-ethical plane applying the category of human fault.
Keywords: engineering and technology; ecological crisis; existential (ecological) human fault